Towards the provision of appropriate maternity spaces in healthcare facilities of Malaysia - spatial studies on the selected maternity units - Mohd Nawawi, Norwina (2005)
Public facilities for maternity care is among the earliest facility provided for the Malaysian public by the British. Maternity care includes pre and post-natal care that were provided as part of the primary care towards secondary care and subsequently a follow-up by the primary care caregivers. Traditionally, maternity care was given in the home. However, with Malaysia driving towards achieving a low mortality rate in childbirth, and control environment can only be obtained in special spaces, Maternity and Child Health Clinics, Alternative Birthing Centres and Labour and Delivery Units of hospitals were established. The contention was brought about among healthcare architects and caregivers on what are ‘adequate’ spaces amidst appropriate and functional spaces. The spatial study is thus aimed to review and analyse what the caregivers meant by ‘adequate’ spaces in meeting the needs of maternity services against the use of natural instincts or gut feelings.